Predicting venous thrombosis in women using a combination of genetic markers and clinical risk factors. (12th January 2015) - Bruzelius, M.; Bottai, M.; Sabater‐Lleal, M.; Strawbridge, R. J.; Bergendal, A.; Silveira, A.; Sundström, A.; Kieler, H.; Hamsten, A.; Odeberg, J.
Summary Background Family history of venous thromboembolism (VTE) has been suggested to be more useful in risk assessment than thrombophilia testing. Objectives We investigated established genetic susceptibility variants for association with VTE and evaluated a genetic risk score in isolation and combined with known trigger factors, including family history of VTE. Patients/Method A total of 18 single nucleotide polymorphisms (SNPs) selected from the literature were genotyped in 2835 women participating in a Swedish nationwide case‐control study (the ThromboEmbolism Hormone Study [TEHS]). Association with VTE was assessed by odds ratios (ORs) with 95% confidence interval (CI) using logistic regression. Clinical and genetic predictors that contributed significantly to the fit of the logistic regression model were included in the prediction models. SNP‐SNP interactions were investigated and incorporated into the models if found significant. Risk scores were evaluated by calculating the area under the receiver‐operating characteristics curve (AUC). Results Seven SNPs (F5 rs6025, F2 rs1799963, ABO rs514659, FGG rs2066865, F11 rs2289252, PROC rs1799810 and KNG1 rs710446) with four SNP‐SNP interactions contributed to the genetic risk score for VTE, with an AUC of 0.66 (95% CI, 0.64–0.68). After adding clinical risk factors, which included family history of VTE, the AUC reached 0.84 (95% CI, 0.82–0.85). The goodness of fit of the genetic and combined scores improved when significant SNP‐SNP interaction terms were included. Conclusion Prediction of VTE in high‐risk individuals was more accurate when a combination of clinical and genetic predictors with SNP‐SNP interactions was included in a risk score.